Photosensitivity of Multilayer Structure with Potential Barriers - Giyasova Feruza Abdiazizovna, Karimov Abdulaziz Vakhitovich, Yodgorova Dilbara Mustafayevna, Abdulkhaev Oybek Abdullazizovich (International Journal of Advanced Science and Technology, 2020)
The paper reports the research results of photosensitivity in Au-vGaAs: O-nCdS-nInP-Au heterojunction structure for various operation modes. Experiments show that irrespective of the excited surface such structures manifest various photosensitivity in the spectral range of 0,85-0,9 μm and 1,31-1,55 μm, which might be due to photon generation processes in high-resistance gallium arsenide and photoemission processes occurring from metal to semiconductor.